ANALYSIS OF THE CHEMICAL EFFECTS OF OLIGOMERIC SUBSTANCES IN OBTAINING MODIFIED ANTI-CORROSION COATINGS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines research on analyzing the chemical effects of obtained oligomeric substances and their application in modified anticorrosive coatings. Anticorrosion coatings play a crucial role in ensuring the long-term use of metal products in modern industry. The chemical and physical properties of oligomeric substances contribute to the creation of highly effective protective materials by enhancing the coatings' adhesion, mechanical durability, and thermal stability. Studies have shown that coatings modified with oligomeric materials are significantly more effective than standard coatings, providing high adhesion, mechanical strength, and corrosion resistance efficiency.